Pengaruh Efikasi Diri dan Kemandirian Belajar Terhadap Pemahaman Konsep Matematika diSMP Islam Al Azhar, Banten - Casidin; Suryana, Andri; Hasbullah (ALFARISI: Jurnal Pendidikan MIPA, 2026)
This study aims to find out: (1) the effect of self-efficacy and learning independence together on the understanding of mathematical concepts; (2) the effect of self-efficacy on the understanding of mathematical concepts; (3) the influence of learning independence on the understanding of mathematical concepts. The research method used is a survey method with correlational analysis conducted on the student population of Al Azhar Islamic Junior High School in Banten province for the 2025/2026 school year. The sample was taken by  the proportion sampling technique  of 83 students. The instruments used are questionnaires and tests. The data is analyzed first by testing the requirements of data analysis. After the data requirements test was met, an inferential analysis was carried out to test the research hypothesis using multiple correlation and regression analysis techniques. From the results of the study, it was found that: (1) there was a significant influence of self-efficacy and learning independence together on the understanding of mathematical concepts of Al Azhar Islamic Junior High School students in Banten province. This is evidenced by a sig value of 0.000 < 0.05 and Fcal = 85.795; 2) there is a significant influence of self-efficacy on the understanding of mathematical concepts of students of Al Azhar Islamic Junior High School in Banten province. This is evidenced by the sig value of 0.000 < 0.05 and tcal = 5.056; (3) there is a significant influence of learning independence on the understanding of mathematical concepts of Al Azhar Islamic Junior High School students in Banten province. This is evidenced by the sig value of 0.000 < 0.05 and tcal = 4.971.
Keywords: pemahaman konsep matematika; efikasi diri; kemandirian belajar